The United States, the Cold War and Indonesia-People's Republic of China Relations, 1950–1955 (KEMANUSIAAN The Asian Journal of Humanities, 2016)
The Cold War in the Third World was certainly much more dynamic than a mere clash of power and ideology between the belligerent big powers. In newly emerging areas like Southeast Asia for instance, many of the newly independent states have made clear from the outset that they do not wish to take sides in the Cold War, wanting to be non-aligned. For the United States, however, the Cold War was an uncompromisable situation and held that nonalignment was self-deception, naïve and even dangerous. This essay examines the interplay between the American policy of containment and the Indonesian policy of non-alignment with particular reference to the United States' reactions to Indonesia's relations with the People's Republic of China (PRC). The discussion covers the period from 1950 through to the Bandung Conference in 1955. An examination of the conflict between the American policy of "containment" and Indonesia's policy of "non-alignment" during the 1950s would serve to illustrate that the Cold War in Asia was much more dynamic that just clashes between the belligerent big powers.